Kształtowanie kadr administracji publicznej w Wielkiej Brytanii - Tracz, Katarzyna (Human resources management within public administration in Great Britain, 2006)
The purpose of this paper is to present the ways of human resources management within public administration in Great Britain. The article starts with the identification of reforms that facilitated the transformation of the public administration model, from the bureaucratic to the managerial one, which is market-oriented. In the next part of the paper the attention is focused on a feature of the British Civil Service, which role is to manage public organizations in a strategic way. A brief description of self-administration and directions it is taking has also been included in this paper. The lasl point of interest is an attempt to evaluate human resources management within public administration in Great Britain and to identify the possible ways of implementing its solutions in Eastern and Central Europe.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 299-306